Pengaruh Kualitas Pelayanan dan Promosi Terhadap Kepuasan Konsumen Pengguna Layanan Grabbike di Kota Harapan Indah Bekasi - Charles Aditya Sunaryo; Vina Meliana (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of service quality on customer satisfaction, the effect of promotion on customer satisfaction and the simultaneous influence of service quality and promotion on customer satisfaction of GrabBike service users in the city of Harapan Indah Bekasi. This research method is quantitative and the data collection process is done by giving a questionnaire. The population in this study are people who live in the city of Harapan Indah Bekasi. The sample was determined by purposive sampling technique and the research sample was 135 respondents. The analysis in the study was carried out using multiple regression techniques with the help of the SPSS version 25 program. The results of the study concluded that service quality variables had an effect on customer satisfaction, promotion variables had an effect on customer satisfaction and simultaneously service quality variables and promotion variables had an effect on customer satisfaction by 62.4 % and the remaining 37.6% is influenced by other variables not found in the study.